Edematogenic and myotoxic activities of the duvernoy’s gland secretion of philodryas olfersii from the north-east region of Argentina - Acosta, Ofelia Cristina; Leiva, Laura Cristina Ana; Peichoto, María Elisa; Maruñak, Silvana Licia; Ruiz, Raquel Mónica; Teibler, Gladys Pamela; Gay, Claudia Carolina; Rey, Laura R. (Sociedad Latinoamericana de Microscopía Electrónica. Centro Regional de Investigaciones Científicas y Tecnológicas, 2003)
Philodryas olfersii is found in South America, from Amazonas to Patagonia. It is important to characterize the venom of P. olfersii, who inhabits the North-East region of Argentina, since snake venoms are known to exhibit considerable variability in composition and biological activities. In this work, mice weighing 18-20 g (n = 4 for each experimental group) were used. For the edematogenic activity mice were injected s.c. in the right foot pad with 50 ml of solutions containing different amounts of venom, whereas the left foot pad was injected with 50 ml of PBS. Two hours after injection mice were killed by cervical dislocation and both feet were cut off and weighed individually. For the myotoxic activity mice were injected i.m. with 100 ml of solutions containing 40 mg of venom. Blood samples were extracted after 1, 3, 6, 8, 10, 12, 14, 16 and 24 h of venom injection to determinate serum CPK activity and mice were sacrif iced at the same time intervals to obtain the inoculated gastrocnemius muscle. They were f ixed with Bouin solution and stained with Hematoxylin-Eosin. Results showed that P. olfersii venom exhibits a high edematogenic activity (MED = 0.31 mg) and a moderate myotoxic activity. Myonecrosis reached its highest level after 12 h of venom injection as shown by plasmatic CPK levels (5,401 ± 330 IU/l) and microscopic assay. It demonstrates the potential toxicity of the venom of P. olfersii, who inhabits the North-East region of Argentina. It also reinforces the original warning concerning the potential danger of bites by colubrids.
Keywords: Philodryas olfersii; Edematogenic activity; Myotoxic activity